An Informational Guide to Common Stony Corals of Florida - Joseph Henry; Roy P. Yanong; Maia McGuire; Joshua T. Patterson (EDIS)
The following information is meant to be a guide to Scleractinian (stony) corals of Florida. All corals presented in this paper are in a protected status under Florida’s Coral Reef Protection Act and several of these species are federally protected under the Endangered Species Act. In their natural environment, these corals should never be handled or touched in any form.